Respiratory tract damage with bocavirus infection in children - E. V. Sharipova; I. V. Babachenko; M. A. Shcherbatyh (LLC "Diagnostics and Vaccines", 2020)
Long time the main pathogens associated with the development of community-acquired pneumonia were bacteria. However, in recent years in the Russian Federation, like all over the world, the view of the damage of lower respiratory tract changed, including a unique approach to community-acquired pneumonia as a bacterial infection, and respiratory viruses have become seen as a direct cause of lower respiratory tract damage, or as part of a viral-bacterial co-infection. These studies became possible since the widespread introduction of PCR techniques in the clinical setting, identification of respiratory viruses has increased and new microorganisms such, one as human bocavirus have been discovered. Objective: to study the features of respiratory tract damage in acute bocavirus infection in children of different ages. Materials and methods: A retrospective analysis of 97 medical hospital documentation of children with acute bocavirus infection, detected confirmed by PCR in nasopharyngeal aspirate. Results: In this work, it was shown that human bocavirus spread throughout the year with an increase in the incidence of clinically significant forms in the autumnwinter period, including during the period of an increase in the incidence of influenza. HBoV infection requiring hospitals is most significant in the first three years of life. In 74.2% of hospitalized children, bocavirus infection occurs with lower respiratory tract infections in the form of bronchitis - 77.8%, pneumonia - 28.9% and rarely bronchiolitis and is complicated by the development of respiratory failure in 28.9% of cases. Changes in the blood test are non-specific, and the level of C-reactive protein in children with various clinical manifestations of HBoV infection generally does not exceed 50 mg / l. An x-ray of the chest organs does not objectively reflect the existing volume and nature of the inflammatory process in the lungs.